THE POLITICAL MODERNIZATION AND ITS FEATURES IN MODERN CHINA AND JAPAN (Journal of Oriental Studies, 2016)
This article examines the main characteristics of political modernization development in China and Japan as a base of its traditional and modern elements interaction in these countries. The authors made an analysis to the preservation level of Confucian ideas in the political life of China and Japan, and studied the role of Confucian ideology in political modernization development of above-mentioned countries.The political modernization in these countries can be considered as the most acceptable alternative to the correlation between the traditions and innovations; therefore, studying this experience will be advantageous for South and Southeast Asian countries, there also could be some useful aspects even for modern Kazakhstan in spite of their specific differences in historical development and contemporary problems.
Keywords: political modernization; traditional society; confucian’s values; political culture.